2022
DOI: 10.3390/ijms23169103
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Biphasic Action of Quetiapine on AMPK Signalling via 5-HT7 Receptor: Exploring Pathophysiology of Clinical and Adverse Effects of Quetiapine

Abstract: Recent pharmacological studies indicated that the modulation of tripartite-synaptic transmission plays important roles in the pathophysiology of schizophrenia, mood disorders and adverse reactions. Therefore, to explore the mechanisms underlying the clinical and adverse reactions to atypical antipsychotics, the present study determined the effects of the sub-chronic administration of quetiapine (QTP: 3~30 μM) on the protein expression of 5-HT7 receptor (5-HT7R), connexin43 (Cx43), cAMP level and intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…Therapeutic-relevant and supratherapeutic serum concentrations of lurasidone are ranged from 30–100 nM and higher than 500 nM, respectively [ 25 , 26 ]. Therapeutic-relevant and supratherapeutic serum concentrations of quetiapine ranged from 0.3–10 μM and higher than 30 μM, respectively [ 19 , 25 , 26 , 27 ]. Based on these clinical findings and preclinical demonstrations, in this study, primary cultured cortical astrocytes were chronically (for 14 d) exposed to supratherapeutic concentration of lurasidone (500 nM) and quetiapine (30 μM) and therapeutic-relevant concentration of lurasidone (100 nM) and quetiapine (3 μM) [ 19 , 20 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therapeutic-relevant and supratherapeutic serum concentrations of lurasidone are ranged from 30–100 nM and higher than 500 nM, respectively [ 25 , 26 ]. Therapeutic-relevant and supratherapeutic serum concentrations of quetiapine ranged from 0.3–10 μM and higher than 30 μM, respectively [ 19 , 25 , 26 , 27 ]. Based on these clinical findings and preclinical demonstrations, in this study, primary cultured cortical astrocytes were chronically (for 14 d) exposed to supratherapeutic concentration of lurasidone (500 nM) and quetiapine (30 μM) and therapeutic-relevant concentration of lurasidone (100 nM) and quetiapine (3 μM) [ 19 , 20 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therapeutic-relevant and supratherapeutic serum concentrations of quetiapine ranged from 0.3–10 μM and higher than 30 μM, respectively [ 19 , 25 , 26 , 27 ]. Based on these clinical findings and preclinical demonstrations, in this study, primary cultured cortical astrocytes were chronically (for 14 d) exposed to supratherapeutic concentration of lurasidone (500 nM) and quetiapine (30 μM) and therapeutic-relevant concentration of lurasidone (100 nM) and quetiapine (3 μM) [ 19 , 20 , 27 , 28 ]. Previously, pharmacodynamic studies reported that the effective dose of systemic administration of lurasidone [ 29 , 30 ] and quetiapine [ 31 ] to schizophrenic models were 1 and 10 mg/kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AMPK controls the metabolism of individual cells in peripheral organs; however, hypothalamic AMPK seems to play fundamental roles in regulating both sides of the energy balances equation (feeding and energy expenditure) in whole-body 5 . Indeed, antipsychotics with a high-risk for weight gain (clozapine and olanzapine) enhance hypothalamic AMPK signalling, whereas lower-risk antipsychotics (lurasidone and brexpiprazole) suppress AMPK signalling [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%